Produção de grão-de-bico adubado com fertilizantes organominerais de lodo de esgoto - Athos Rodrigues Soares Viana (2022)
The production and use of organomineral fertilizers coming from sewage sludge can contribute to the growth and production of chickpeas, in addition to providing adequate disposal for this urban waste. The study aimed to produce organomineral fertilizers (FOM) based on sludge and to evaluate the production of chickpeas submitted to fertilization with FOM. The initial stage of the study consisted of producing organomineral fertilizers in powder or granular form using two organic sources of sludge (composted sludge and sludge biochar) and simple sources of mineral fertilizers containing N, P and K (urea, MAP and chloride of potassium). The second stage consisted of using these fertilizers in the cultivation of chickpeas of the BRS Aleppo variety. The experiment was designed in randomized blocks, with five replications, in a 2x2+2 analysis scheme, consisting of two organic sources for the production of organomineral fertilizer (composted sludge - LC or sludge biochar - BL), two forms of fertilizer (granulated or powder) and two additional controls (mineral fertilization with NPK in the proportion 04:15:04 and T-control). To set up the study in a greenhouse were used 30 pots containing 4 dm3 of a Cambisoil, mixed with sand in a 1:1 ratio (soil:sand). Two plants per pot were grown for 122 days. Being that, during the experimental installation were carried out cover fertilization and cultural practices (deionized water, manual removal of weeds and insect pests). Plants harvested were carried out by collecting the entire plant (roots, shoots, grains, straw) and the plant parts were dried in an oven with forced ventilation (60-65°C) until constant weight was obtained. They were also collected samples and soil for the characterization of chemical attributes. The organomineral fertilization with composted sludge and sludge biochar, in powder or granular form, favored the physiological variable total chlorophyll index and incremented the production characteristics (root dry matter, grains, shoots, total, plant residues) compared to the treatment without fertilization (T), and provided averages similar to those found in the soil fertilized with NPK mineral fertilizer. The application of granulated or powdered fertilizer did not differ between them for most of the studied variables. The results obtained make it possible to infer that the use of organomineral fertilizer based on sludge presents a production potential for chickpea similar to that obtained in the managements that received only mineral fertilization, therefore, the use of sludge can be considered an alternative of management for formulation of organomineral fertilizers and technical recommendations on agricultural crops.